RANTES and SDF-1 Are Keys in Cell-based Therapy of TMJ Osteoarthritis. (November 2015) - Lu, L.; Zhang, X.; Zhang, M.; Zhang, H.; Liao, L.; Yang, T.; Zhang, J.; Xian, L.; Chen, D.; Wang, M.
The present study aimed to investigate the therapeutic effect of injections of local bone marrow mesenchymal stem cells (BMSCs) on osteoarthritis (OA) of the temporomandibular joint (TMJ) and to explore the role of stromal cell–derived factor 1 (SDF-1) and regulated on activation, normal T-cell expressed and secreted (RANTES) in this effect. Fundamentally, OA of the TMJ was induced by unilateral anterior crossbite in mice. Exogenous green fluorescent protein–labeled BMSCs (GFP-BMSCs) were weekly injected into the TMJ region for 4, 8, and 12 wk. The reparative effects of exogenous GFP-BMSCs were investigated by morphological observation and micro–computed tomography. The differentiation of GFP-BMSCs in the cartilage was examined by double immunofluorescence of GFPs with type II collagen, and the expression of related factors in the condylar cartilage was quantified by real-time polymerase chain reaction. The role of RANTES and SDF-1 in the therapeutic effect of exogenous BMSCs was examined by both in vitro and in vivo studies. The OA cartilage of the TMJ displays a synchronous increase in SDF-1 and RANTES expression and a higher capability of attracting the migration of GFP-BMSCs. The implanted GFP-BMSCs differentiated into type II collagen–positive cells and reversed cartilage degradation and subchondral bone loss in mice with OA of the TMJ. The migration of GFP-BMSCs towards OA cartilage and the rescuing effect of GFP-BMSC injections were impaired by the inhibitors of C-X-C chemokine receptor type 4 (CXCR4) and C-C chemokine receptor type 1 (CCR1), which are the receptors of SDF-1 and RANTES, respectively. Our data indicated that SDF-1/CXCR4 and RANTES/CCR1 signals are pivotal and function synergistically in the recruitment of GFP-BMSCs towards degraded cartilage in mice OA of the TMJ.